2020
DOI: 10.1590/1678-4685-gmb-2018-0162
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in populations of African mahogany (Khaya grandioliola C. DC.) introduced in Brazil

Abstract: Given its high-valued wood, the African mahogany (Khaya grandifoliola) has been envisaged as a renewable source of tropical hardwoods in Brazil. However, there are concerns about the hypothesized low diversity among the few K. grandifoliola germplasm sources introduced in the country. Using eight microsatellite markers, we evaluated the genetic diversity and divergence among 53 superior trees selected from three provenances of K. grandifoliola located in the state of Pará. These populations are among the oldes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is not clear if this value reflects a positive selection for heterozygotes in the residual population, which might be possible if the SNPs are linked to loci under selection 24 . Previous genetic diversity studies of Khaya grandioliola also revealed such an excess of heterozygotes, with a relatively large negative inbreeding coefficient ( F i = −0.31) estimated from 53 superior trees from three provenances in Brazil 37 . Furthermore, if the inbreeding coefficient is negative after roguing, it would suggest than more homozygotes than heterozygotes have been removed, which indeed could be a result of slight inbreeding depression.…”
Section: Discussionmentioning
confidence: 80%
“…It is not clear if this value reflects a positive selection for heterozygotes in the residual population, which might be possible if the SNPs are linked to loci under selection 24 . Previous genetic diversity studies of Khaya grandioliola also revealed such an excess of heterozygotes, with a relatively large negative inbreeding coefficient ( F i = −0.31) estimated from 53 superior trees from three provenances in Brazil 37 . Furthermore, if the inbreeding coefficient is negative after roguing, it would suggest than more homozygotes than heterozygotes have been removed, which indeed could be a result of slight inbreeding depression.…”
Section: Discussionmentioning
confidence: 80%
“…), which has great production potential, high commercial value, and low incidence of pests. African mahogany, which was previously introduced in Brazil, has a wide genetic diversity that is comparable to that of natural species (Soares et al 2020). The growing demand for tropical wood from reputable and responsible origins has led to new investments in plantations throughout the country, ultimately directing the forest market toward new potential species (Reis et al 2019).…”
Section: Biometric Assessment Of Early Stem Growth At a Commercial St...mentioning
confidence: 99%
“…is a high sized heliophile tree, reaching 40 meters in height, featured by a brownish-pink wood, currently planted in many regions of Brazil (Reis et al, 2019). The species K. grandifoliola has a broad brazilian introduced genetic diversity, promptly available to be explored silviculturally (Soares et al 2020). For many years been mistakenly treated as Khaya ivorensis.…”
Section: Introductionmentioning
confidence: 99%